A Review Paper on EDM Parameter of Composite material and Industrial Demand Material Machining. (2018) - Selvarajan, L.; Rajavel, J.; Prabakaran, V.; Sivakumar, B.; Jeeva, G.
Abstract: Electric discharge machining (EDM) the one type of Electrical energy based Machining process, in a modern world EDM is has lot of challenge against to machine hard material and complex shape structure. In this investigation, the input parameters such as Pulse on time, Pulse off time, Peak current and output parameters such as Metal removal rate (MRR), Surface roughness (SR), Tool or electrode wear ratio (TWR) are deeply focused in the past researchers and investigation. The objective of this paper to review the past researches and develop the way for advance Research.